Preparation method of covalent organic framework material and application of covalent organic framework material in tin-air battery

By using covalent organic framework materials as protective films on the tin anode of tin-air batteries, the problem of tin anode corrosion and "dead tin" falling off at high temperatures is solved, significantly improving battery performance.

CN119350566APending Publication Date: 2025-01-24KUNMING UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411480135.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The problem of degradation in performance of tin air batteries at high temperatures is mainly due to the corrosion of the tin anode and the shedding of "dead tin", which leads to the depletion of tin ions in the electrolyte.

Method used

The common price organic framework material (COFS) is used as the protective film of the tin anode, and a uniform and dense protective film is formed on the surface of the tin tablet through the original growth method to reduce the corrosion of the tin anode and the "dead tin".

Benefits of technology

Effectively alleviate the corrosion of electrolyte on the surface of the tin anode, suppress the "dead tin" falling off, improves the electronic conductivity at high temperature, and improves the performance of tin air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350566A_ABST
    Figure CN119350566A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a covalent organic framework material and application of the covalent organic framework material in a tin-air battery, and the preparation method comprises the following steps: dispersing 2, 2 '-bis (trifluoromethyl) diaminobiphenyl in a mixed solution of 1, 3-dioxolane and ethylene glycol dimethyl ether to obtain a solution I; 2, 4, 6-triformyl phloroglucinol is dispersed in a tetraethylene glycol dimethyl ether solution, and a solution II is obtained; dripping the solution I on a polished tin sheet; after the solution is volatilized, dripping the solution II at the same position; reacting at room temperature for 12 hours, washing with a tetrahydrofuran solution for one time, and washing with a mixed solution of 1, 3-dioxolane and ethylene glycol dimethyl ether for 1-3 times; and then carrying out vacuum drying at room temperature for 8-12h, and finally preparing the covalent organic framework material on the tin sheet. According to the invention, an in-situ preparation method is adopted, the covalent organic framework film and the tin anode are compounded together, and the tin anode is separated from the electrolyte by the film, so that the corrosion of the electrolyte to the anode in room-temperature and high-temperature environments can be reduced, and the formation of by-products and dead tin on the surface of the anode is reduced to improve the battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a preparation method of a covalent organic framework material and an application thereof in a tin-air battery. Background Art

[0002] The limited supply of lithium resources on Earth and the toxicity and flammability of organic electrolytes have hindered the further development of lithium-ion batteries. Secondary tin-air batteries (SABs) are a special type of fuel cell that uses oxygen in the air as the active material and tin as the negative electrode. They have the characteristics of low cost, environmental protection and high safety. In addition, tin metal has a high theoretical capacity (451.6 mAh g -1 ) and low redox potential (-0.14V vs. standard hydrogen electrode, SHE) can release high energy in aqueous electrolytes (Adv. Mater. 2024, 36, 2408067; J. Am. Chen. Soc. 2023, 145, 10880-10889). However, the close contact between the electrolyte and the tin electrode causes large and irregular tin particles to fall off the substrate and produce "dead tin", thereby depleting the tin ions in the electrolyte, ultimately leading to reduced battery performance or failure. This phenomenon is more obvious at high temperatures. Therefore, processing the tin anode to optimize the grain size of the Sn particles and improve the deposition uniformity is a feasible solution to improve battery performance and temperature adaptability. There is currently no report on the use of tin anode protection film to optimize tin-air batteries.

[0003] Covalent organic frameworks (COFs) are a new type of porous organic material formed by connecting organic units together through dynamic covalent bonds. Compared with traditional inorganic materials, COFs have the characteristics of diverse structures and tunable properties, making them ideal materials for developing high-performance electrode materials. However, most of the COFs reported as protective films for metal anodes (zinc, lithium) are prepared by solvothermal methods into powders and then constructed by complex mixing with polymer binders. This may lead to uneven distribution of COFs and affect their stabilizing effect on the anode.

[0004] Therefore, how to better apply covalent organic framework materials to the anode of tin-air batteries to reduce the corrosion of the tin anode and inhibit the shedding of "dead tin", and improve the performance of tin-air batteries at high temperatures has become a problem that needs to be solved at present. Summary of the invention

[0005] The purpose of the present invention is to solve the defects of the above-mentioned prior art and provide a method for preparing a covalent organic framework material and its application in tin-air batteries.

[0006] According to one object of the present invention, the present invention provides a method for preparing a covalent organic framework material, comprising the following steps:

[0007] S1, dispersing 2,2'-bis(trifluoromethyl)diaminobiphenyl in a 1,3-dioxolane and ethylene glycol dimethyl ether solution to obtain a solution I;

[0008] S2, dispersing 2,4,6-triformylphloroglucinol in tetraethylene glycol dimethyl ether solution to obtain solution II;

[0009] S3, dropping solution I on the polished tin sheet;

[0010] S4, after the solution evaporates, add solution II dropwise at the same position;

[0011] S5. After reacting at room temperature, washing with tetrahydrofuran solution once, and washing with 1,3-dioxolane and ethylene glycol dimethyl ether solution 1 to 3 times;

[0012] S6. Subsequently, vacuum drying is performed at room temperature for 8 to 12 hours to finally obtain a covalent organic framework material on the tin sheet.

[0013] Furthermore, the volume ratio of solution I to solution II is 0.8 to 1.2.

[0014] Furthermore, the concentration of the solution I is 6×10 -3 M~12×10 -3 M, the concentration of solution II is 4×10 - 3 M~8×10 -3 M.

[0015] Furthermore, the reaction conditions of the solution I and the solution II are 15-30° C. for 10-14 hours.

[0016] Furthermore, in the solution I, the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 0.8 to 1.2.

[0017] According to another object of the present invention, the present invention provides a covalent organic framework material, which is prepared by the above method.

[0018] According to the third object of the present invention, the present invention provides the use of the above covalent organic framework material, which is used to prepare a tin-air battery anode.

[0019] Furthermore, the application of the covalent organic framework material comprises the following steps:

[0020] S1, growing the covalent organic framework material in a thin film on the surface of the tin sheet by an in-situ growth method to form a composite material consisting of the tin sheet and the covalent organic framework material;

[0021] S2, drying the obtained composite material under vacuum at room temperature for 8 to 12 hours, and using the dried composite material as a raw material for a tin-air battery anode.

[0022] Furthermore, the covalent organic framework material is used to prepare a tin-air battery anode.

[0023] Furthermore, the tin-air battery is prepared by using the tin-air battery anode, water-based / solid electrolyte and air cathode.

[0024] Beneficial effects:

[0025] 1. Most materials used as metal anode protective films are prepared into powders by a solvothermal method and then constructed by complexly mixing them with polymer binders. This may lead to uneven distribution of materials and affect their stabilizing effect on the anode. The TpFBD prepared by the present invention forms a uniform and dense protective film on the tin anode by an in-situ growth method, which alleviates the corrosion of the electrolyte on the surface of the tin anode, inhibits the problem of "dead tin" falling off, and improves the electronic conductivity of TpFBD@Sn at high temperatures, thereby improving the performance of the battery at high temperatures.

[0026] 2. The present invention adopts an in-situ growth method to compound the COF material TpFBD with the tin anode. Since TpFBD contains uniform tin-affinity sites (N, O) and a large amount of F, Sn is induced at the tin-affinity sites. 2+ After uniform deposition, Sn 2+ The free F from TpFBD - The reaction generates SnF2, which dissociates during the tin stripping process. 2+ Migrate to the cathode. Sn 2+ The strong interaction with TpFBD prevents Sn 2+ It reacts with the electrolyte to generate by-products, which not only inhibits the occurrence of side reactions but also increases the Sn 2+ The utilization rate of the battery ultimately improves the battery performance.

[0027] 3. The present invention adopts an in-situ growth method to generate a thin film, so that the thin film can be uniformly grown on the surface of the tin sheet, and the thin film is in close contact with the tin sheet and is not easy to fall off. The method provided by the present invention has a simple and reliable process and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The molecular formula of the TpFBD material prepared in Example 1;

[0029] Figure 2 Fourier transform infrared spectrum (FTIR) of the TpFBD@Sn composite material prepared in Example 1;

[0030] Figure 3 Plane electron microscopy image of the TpFBD@Sn composite material prepared in Example 1;

[0031] Figure 4 Cross-sectional electron micrograph of the TpFBD@Sn composite material prepared in Example 1;

[0032] Figure 5(a) shows the current density of 1 mA / cm 2 The cycling stability comparison of the composite tin-air battery and the blank tin-air battery is shown in Figure 5(b) at a current density of 1 mA / cm 2 , Comparison of the cycle stability of the composite tin-air battery and the blank tin-air battery at a temperature of 50°C. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] The present invention provides a method for preparing a TpFBD@Sn composite material, comprising:

[0036] 1) 2,2'-bis(trifluoromethyl)diaminobiphenyl (FBD) was dispersed in 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (0.8-1.2) solution; the concentration was 6×10 -3 M~12×10 -3 M.

[0037] 2) Disperse 2,4,6-triformylphloroglucinol (Tp) in tetraethylene glycol dimethyl ether (TEGDME) solution; the concentration is 4×10 -3 M~8×10 -3 M.

[0038] 3) A polished tin sheet with a diameter of 15 mm was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 minutes respectively to remove impurities on its surface.

[0039] 4) Take 20 μL of the mixed solution obtained in step 1) and slowly drip it onto the surface (polished surface) of the tin sheet obtained in step 3).

[0040] 5) After the solution added in step 4) evaporates, take 20 μL of the mixed solution obtained in step 2) and slowly drop it to the same position where the solution was added in step 4), and react at 15-30° C. for 10-14 hours.

[0041] 6) The composite material obtained in step 5) is washed once with a tetrahydrofuran solution, and washed 1 to 3 times with a 1,3-dioxolane and ethylene glycol dimethyl ether (0.8 to 1.2) solution.

[0042] 7) The composite material obtained in step 6) is dried under vacuum at room temperature for 8 to 12 hours to finally obtain a TpFBD@Sn composite material

[0043] The preparation method of the composite of TpFBD and tin sheet provided by the present invention can also be used for silicon sheet, lithium sheet, zinc sheet, magnesium sheet, aluminum sheet and the like.

[0044] Example 2

[0045] A polished tin sheet with a diameter of 15 mm was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 minutes respectively to remove impurities on its surface. 17.29 mg of 2,2'-bis(trifluoromethyl)diaminobiphenyl (FBD) was dispersed in 6 ml of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (1:1) solution to obtain solution I; 7.57 mg of 2,4,6-triformylphloroglucinol (Tp) was dispersed in 6 mL of tetraethylene glycol dimethyl ether (TEGDME) solution to obtain solution II; 20 μL of solution I was dropped on the surface of the treated tin sheet, and after the solution evaporated, 20 μL of solution II was dropped at the same position; after reacting at 15°C for 12 hours, it was washed once with tetrahydrofuran solution and washed twice with 1,3-dioxolane and ethylene glycol dimethyl ether (1:1) solution; then it was vacuum dried at 25°C for 12 hours to finally obtain the TpFBD@Sn composite material.

[0046] Figure 1 The molecular formula of the TpFBD@Sn composite material prepared in Example 1 is: Figure 2 Fourier transform infrared spectrum (FTIR) of the TpFBD@Sn composite material prepared in Example 1; Figure 3 Plane electron microscopy image of the TpFBD@Sn composite material prepared in Example 1, Figure 4 The cross-sectional electron micrograph of the TpFBD@Sn composite material prepared in Example 1; Figure 1 , 2 As shown in FIG. 1 , the obvious C=C peak and CN peak in the spectrum prove the synthesis of TpFBD; Figure 3 , Figure 4As shown, by observing the microscopic morphology of the surface and cross-section of the TpFBD@Sn composite material through SEM, it can be found that the TpFBD film has been successfully grown on the tin sheet to form a battery anode.

[0047] Example 3

[0048] A polished tin sheet with a diameter of 15 mm was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 minutes respectively to remove impurities on its surface. 17.29 mg of 2,2'-bis(trifluoromethyl)diaminobiphenyl (FBD) was dispersed in 6 ml of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (1:0.8) solution to obtain solution I; 7.57 mg of 2,4,6-triformylphloroglucinol (Tp) was dispersed in 6 mL of tetraethylene glycol dimethyl ether (TEGDME) solution to obtain solution II; 18 μL of solution I was dropped on the surface of the treated tin sheet, and after the solution evaporated, 18 μL of solution II was dropped at the same position; after reacting at 20°C for 13 hours, it was washed once with tetrahydrofuran solution and washed 3 times with 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (1:0.8) solution; then it was vacuum dried at 25°C for 12 hours to finally obtain the TpFBD@Sn composite material.

[0049] Example 4

[0050] A polished tin sheet with a diameter of 15 mm was ultrasonically cleaned in acetone, anhydrous ethanol and deionized water for 15 minutes respectively to remove impurities on its surface. 17.29 mg of 2,2'-bis(trifluoromethyl)diaminobiphenyl (FBD) was dispersed in 6 ml of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (1.1:1) solution to obtain solution I; 7.57 mg of 2,4,6-triformylphloroglucinol (Tp) was dispersed in 6 mL of tetraethylene glycol dimethyl ether (TEGDME) solution to obtain solution II; 20 μL of solution I was dropped on the surface of the treated tin sheet, and after the solution evaporated, 20 μL of solution II was dropped at the same position; after reacting at 25°C for 12 hours, it was washed once with tetrahydrofuran solution and twice with 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) (1.1:1) solution; then it was vacuum dried at 25°C for 8 hours to finally obtain the TpFBD@Sn composite material.

[0051] Example 5

[0052] Electrolyte and cathode preparation:

[0053] Take 2-4 mg of platinum-carbon catalyst, add 700 μL of Nafion solution and 300 μL of isopropanol solution in turn, mix thoroughly, and ultrasonicate in an ultrasonic machine at a temperature below 40°C for 0.5-1h until the solution becomes viscous, then use a pipette to apply it on carbon paper. When spin coating, every 200 μL can apply a cathode with a diameter of 10-20 mm. Stir acrylamide, N-N'methylenebisacrylamide, potassium persulfate and carboxymethyl cellulose with a mass ratio of 2000:2:5:175 in a mixed solution of dimethyl sulfoxide and deionized water with a volume ratio of 1:1 for 1-3h (the stirring speed is 500r / min). Invert the mixed solution into a glass container and dry it in a vacuum oven at 60°C for 12h, then add 20ml-25ml 6M KOH+0.02M SnO2 2- The mixed solution was soaked for 72h to 96h to obtain carboxymethyl cellulose organic gel electrolyte (GPEs). The TpFBD@Sn composite material, carboxymethyl cellulose organic GPEs and Pt / C cathode were sequentially placed into a button battery mold for assembly, and then packaged using a packaging machine to finally obtain a tin-air button battery.

[0054] Figure 5(a) shows the current density of 1 mA / cm 2 When the temperature is room temperature (25°C), the cycle stability comparison of the composite tin-air battery and the blank tin-air battery. As shown in Figure 5(a), at 1mA / cm 2 At a current density of 1 mA / cm and 25 °C, the TpFBD@Sn composite battery showed a low charging voltage of 1.34 V compared with the battery assembled with blank tin sheet (2.1 V), which was 0.76 V lower than that of the blank battery. 2 , when the temperature is 50℃, the cycle stability comparison of the composite tin-air battery and the blank tin-air battery is shown in Figure 5(b). 2 At 50°C, the charging voltage of the battery assembled with TpFBD@Sn composite material is about 1.5V, which is not much different from the charging voltage at room temperature. This is because the electronic conductivity of TpFBD@Sn is improved at high temperature. At the same time, carboxymethyl cellulose organic GPEs have good water retention and ionic conductivity at high temperature.

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a covalent organic framework material, characterized in that: The steps include: S1, dispersing 2,2'-bis(trifluoromethyl)diaminobiphenyl in a 1,3-dioxolane and ethylene glycol dimethyl ether solution to obtain a solution I; S2, dispersing 2,4,6-triformylphloroglucinol in tetraethylene glycol dimethyl ether solution to obtain solution II; S3, dropping solution I on the polished tin sheet; S4, after the solution evaporates, add solution II dropwise at the same position; S4. After reacting at room temperature, washing with tetrahydrofuran solution once, and washing with 1,3-dioxolane and ethylene glycol dimethyl ether solution 1 to 3 times; S5. Subsequently, vacuum drying is performed at room temperature for 8 to 12 hours to finally obtain a covalent organic framework material on the tin sheet.

2. The method for preparing a covalent organic framework material according to claim 1, characterized in that: The volume ratio of the solution I to the solution II is 0.8 to 1.

2.

3. The method for preparing a covalent organic framework material according to claim 1, characterized in that: The concentration of solution I is 6×10 -3 M~12×10 -3 M, the concentration of solution II is 4×10 -3 M~8×10 -3 M.

4. The method for preparing a covalent organic framework material according to claim 1, characterized in that: The reaction conditions of the solution I and the solution II are 15-30° C. for 10-14 hours.

5. The method for preparing a covalent organic framework material according to claim 1, characterized in that: In the solution I, the volume ratio of 1,3-dioxolane to ethylene glycol dimethyl ether is 0.8-1.

2.

6. A covalent organic framework material, characterized in that: Prepared according to any one of claims 1 to 5.

7. The use of the method for preparing a covalent organic framework material according to any one of claims 1 to 5, characterized in that: Used in the preparation of tin-air battery anodes.

8. The use according to claim 7, characterized in that: The steps include: S1, growing the covalent organic framework material in a thin film on the surface of the tin sheet by an in-situ growth method to form a composite material consisting of the tin sheet and the covalent organic framework material; S2, drying the obtained composite material under vacuum at room temperature for 8 to 12 hours, and using the dried composite material as a raw material for a tin-air battery anode.

9. The use according to claim 8, characterized in that: Used to prepare the obtained tin-air battery anode.

10. The use according to claim 8, characterized in that: The tin-air battery is prepared by using the tin-air battery anode, water system / solid electrolyte and air cathode.

Citation Information

Cited By

  • Fluorine-functionalized organic framework material as well as preparation and application thereof

    CN119955048A

  • Fluorine-functionalized organic framework material, preparation and use thereof

    CN119955048B